2016
DOI: 10.1007/s10384-015-0421-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for ocular complications caused by anticancer drug S-1

Abstract: Older patients were at greater risk of S-1-related ocular complications, but these complications were not associated with total administration days or total dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Other ocular complications due to S-1 include lacrimal duct obstruction, 812 corneal abnormalities, 7,8,11 and conjunctival disorders. 10…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other ocular complications due to S-1 include lacrimal duct obstruction, 812 corneal abnormalities, 7,8,11 and conjunctival disorders. 10…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study has yet reported conjunctival findings of fluorescein staining among patients administered S-1. However, conjunctivitis associated with S-1 administration 10 is thought to be due to a complex disorder including drug-induced impairment, corneal disorders, meibomian gland dysfunction, and lacrimal obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S-1, an oral antineoplastic agent containing the prodrug 5-fluorouracil (5-FU), is a popularly used cancer drug especially in Japan. Ocular complications of 5-FU include superficial punctate keratitis (SPK), sheet-like appearance, epithelial erosion, epithelial crack lines, lacrimal duct blockage, and conjunctivitis have also been reported [4,5]. One of pharmacological compounds of S-1, tegafur, becomes 5-FU when it is metabolized in the blood.…”
Section: Casementioning
confidence: 99%
“…Otherwise, in the ocular surface, 5-FU in the lacrimal fluid may induce damages to corneal epithelial cells and stem cells. In Table 1, we present another drug that may induce corneal disorders [3][4][5][6][7][8][9][10][11].…”
Section: Casementioning
confidence: 99%